Factors Associated with the Success of Initial Non-surgical Root Canal Treatment Performed by Dental Postgraduates - Phumkarn, Thapanan; Wessayasatit, Sasiwan (Journal of The Department of Medical Services, 2022)
Background: The study of the success of root canal treatment is important for prognostication and decisionmaking for treatment planning. However, the study of the success rate and factors associated with initial non-surgicalroot canal treatment performed by dental postgraduates at the Institute of Dentistry have never been evaluated. Objective: The aim of this research was to evaluate the success and factors associated with initial non-surgical rootcanal treatment performed by dental postgraduates at the Institute of Dentistry, Ministry of Public Health, from2016 to 2020. Method: A retrospective study was done by collecting data from treatment and radiographic records.Radiographs obtained at pre-operation and the follow-up periods were collected following the Periapical index.The treatment outcome was evaluated to be a success or a failure based on the clinical and radiographic criteria.Factors associated with the treatment were analyzed using chi-square and multiple logistic regression. Result: Therecall rate was 65.2%, ranging from 6 to 52 months, The success rate was 81.7%, the failure rate was 18.3%, and thefunctional rate was 96.6%. The factor significantly associated with initial non-surgical root canal treatment was thepre-operative periapical lesion, in which teeth without any pre-operative periapical lesion had a chance of successmore than teeth with pre-operative periapical lesion < 5 mm and ≥ 5 mm, with the odds ratio of 0.07 and 0.37,respectively. Conclusion: The success rate of initial non-surgical root canal treatment was 81.7% and the failure ratewas 18.3%. The pre-operative periapical lesion was significantly associated with the success of initial non-surgicalroot canal treatment.